Macro and Micro Environmental Perspectives on the Ability of SME Business to Innovate and Perform Good - Muthia Algarini; Dito Aditia Darma Nasution (Future Science, 2023)
The production environment has changed to a knowledge and technology system, and competition has also developed into a more global and innovation system, becoming a competitive environment in most countries and businesses. Companies must evolve and innovate to deal with intense competition and shifting consumer demands if they hope to succeed over the long term in today's global market economy. Small and medium enterprises should seek new business motivations and strategies to better develop new goods and services and take new information and technological advances into account. For a business to grow, innovation is essential. The traditional innovation literature, first published in 1934 by Joseph Schumpeter, focuses on the manufacturing sector and the level of competition in advanced markets and economies. Compared to other countries, Indonesia has a much higher proportion of small businesses per capita. Over the years, SMEs have made a significant contribution to developing countries in Asia (including ASEAN). SMEs are cited in ASEAN countries as a key driver of economic growth and development, the foundation of the national economy, the highest paying industry, and a potential tool for reducing poverty. Especially after the Asian financial crisis, including Indonesia's SMEs which are strategic in private sector growth.